Ocular inoculation of toad venom: toxic cataract and proteomic profiling - Lyu, Danni; Ni, Shuang; Xu, Jia; Zhu, Sha; Xu, Jing-Wei; Feng, Yixuan; Shi, Ce; Xu, Wen (Frontiers in Medicine, 2025)
PurposeTo report a singular case of cataract caused by toad venom inoculation and to scrutinize the pathological mechanisms through proteomic sequencing of the lens specimen.MethodsA young Chinese male presented with progressively deteriorating vision in his right eye subsequent to a history of toad venom inoculation. He was diagnosed with a toxic cataract, and underwent phacoemulsification cataract surgery. Anterior capsule, nucleus, and cortex specimens from the patient (designated as PT_CAP, PT_PHACO, and PT_CTX, respectively) and age-related cataract controls (C_CAP, C_PHACO, and C_CTX, respectively) were collected and subjected to 4D label-free quantitative proteomics.ResultsA multitude of differentially expressed proteins (DEPs) were identified in the patient’s lens compared to those in the controls. Specifically, a total of 204 DEPs were identified in PT_CAP compared to C_CAP, with MYH6, MYL2, MYL3, STAT1, and ANK1 among the foremost regulated DEPs. The DEPs of PT_CAP were principally affiliated with functions including “transportation of small molecules,” “regulation of metal ion transport,” and “import into cell.” A sum of 109 DEPs were delineated in PT_CTX compared to C_CTX, with TPM1 among the top-10 downregulated DEPs. Ninety-five DEPs were pinpointed in PT_PHACO compared to C_PHACO, with hexokinase among the top 10 downregulated DEPs. These proteins were ascertained to be linked with Na+/K+-ATPase activity.ConclusionThis study introduced the first documented case of toxic cataract caused by toad venom inoculation. Proteomic sequencing indicated a correlation between cataract and alterations in Na+/K+-ATPase activity, providing insights for the clinical management of ocular toad venom inoculation in subsequent cases.